FRI0590 Early Recruitment To "Cloudy with A Chance of Pain"; from Website Hits To Smartphone App Downloads. (15th July 2016) - Patel, R.; Sergeant, J.; McBeth, J.; Schultz, D.; Sanders, C.; Cook, L.; Ainsworth, J.; Dixon, W.
Abstract : Background: Traditionally, participant recruitment for observational studies occurs by clinical teams identifying and approaching eligible patients. The current digital age, with increasing access to the web via PCs, tablets and smartphones provides an exciting alternative recruitment strategy. However, it is not clear whether studies can successfully recruit large numbers of participants in this way. "Cloudy with a Chance of Pain" is a national prospective population study which utilises participant's own smartphones to connect daily symptoms and hourly local weather using global positioning system (GPS) and is recruiting participants without the involvement of their clinical teams. Objectives: To describe website activity and subsequent participant enrolment in the first week of recruitment following two national television broadcasts featuring the study. Methods: Cloudy with a Chance of Pain was featured on BBC Two's "Trust Me I'm a Doctor" (20th January 2016) and BBC One's "Breakfast" (26th January 2016). Potential participants were directed to the study website www.cloudywithachangeofpain.com . The landing page described the project in text and video, after which interested visitors were directed to click through each item of an eligibility questionnaire (age ≥17 years, have arthritis or other chronic pain, resident in the UK, own a smartphone). If eligible in all 4, they were instructed to download the study app. Following download, participants were required to consent and then complete a baseline questionnaire. Google Analytics was used to evaluate the pattern and frequency of website traffic since launch. Enrolment data was provided by the data custodians and app developers, uMotif. Results are reported as mean (SD) or number (%). Results: Within one week of launch, there were 84, 494 visits from 22, 732 visitors to the landing page of the website. There were 22, 046 views of the "Take Part" page. The "take part" eligibility questionnaire was completed on 18, 631 occasions. Of those, 15, 836 (85%) were determined eligible. 5, 683 participants successfully enrolled after following instructions to download the app and provide consent. 4, 433 (78%) participants were female. The mean age was 49 (13). Figure 1 demonstrates cumulative enrolment within the first 7 days of launch. 48% of all enrolees registered within 3 hours of either the first or second TV broadcast. Conclusions: Early recruitment to this study has been highly successful without any involvement of clinical teams. Although high website activity has been enabled by national media coverage, we have noted an excellent conversion rate (>33%) from website activity to app downloads without offering personal support or incentives. This confirms that direct participant recruitment using website information and smartphones is a novel and potentially successful approach to patient recruitment to observational studies. Acknowledgement: Arthritis Research UK and uMotif Ltd. Disclosure of Interest: None declared